Identification of novel QTL associated with soybean isoflavone content - Ruili Pei; Jingying Zhang; Ling Tian; Shengrui Zhang; Fenxia Han; Shurong Yan; Lianzheng Wang; Bin Li; Junming Sun (Crop Journal, 2018)
Soybean isoflavones are essential secondary metabolites synthesized in the phenylpropanoid pathway and benefit human health. In the present study, high-resolution QTL mapping for isoflavone components was performed using specific-locus amplified fragment sequencing (SLAF-seq) with a recombinant inbred line (RIL) population (F5:7) derived from a cross between two cultivated soybean varieties, Luheidou 2 (LHD2) and Nanhuizao (NHZ). Using a high-density genetic map comprising 3541 SLAF markers and the isoflavone contents of soybean seeds in the 200 lines in four environments, 24 stable QTL were identified for isoflavone components, explaining 4.2%–21.2% of phenotypic variation. Of these QTL, four novel stable QTL (qG8, qMD19, qMG18, and qTIF19) were identified for genistin, malonyldaidzin, malonylgenistin, and total isoflavones, respectively. Gene annotation revealed three genes involved in isoflavone biosynthesis (Gm4CL, GmIFR, and GmCHR) and 13 MYB-like genes within genomic regions corresponding to stable QTL intervals, suggesting candidate genes underlying these loci. Nine epistatic QTL were identified for isoflavone components, explaining 4.7%–15.6% of phenotypic variation. These results will facilitate understanding the genetic basis of isoflavone accumulation in soybean seeds. The stable QTL and tightly linked SLAF markers may be used for marker-assisted selection in soybean breeding programs. Keywords: Soybean (Glycine max L. Merrill), QTL mapping, Isoflavones, Specific-locus amplified fragment sequencing (SLAF-seq)